2003
DOI: 10.1007/s00464-002-8957-9
|View full text |Cite
|
Sign up to set email alerts
|

Totally extraperitoneal repair of recurrent inguinal hernia

Abstract: Although for its definitive management, recurrent hernia requires a reliable operative technique, current data do not support the recommendation of any of the currently available procedures as the gold standard. In a representative patient population with recurrent hernia, we were able to demonstrate that TEP achieves very good results in terms of re-recurrence rate, intraoperative and postoperative complications, and rehabilitation. Prerequisites for the reliable and low-complication application of the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
3
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
3
37
3
1
Order By: Relevance
“…17 According to our results, peritoneal tearing occurred more frequently in the recurrent hernia group than that in the primary hernia group, and the operation time was longer in the recurrent hernia group. One hundred and six cases of peritoneal tearing occurred (30% in the recurrent hernia group and 7.8% in the primary hernia group), but this was similar or even lower, compared to the rate of peritoneal tearing, in other studies (26% in the adhesions group versus 18% in the no-adhesions group 5 and 46% in the recurrent hernia group versus 28% in the primary hernia group 13 ).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…17 According to our results, peritoneal tearing occurred more frequently in the recurrent hernia group than that in the primary hernia group, and the operation time was longer in the recurrent hernia group. One hundred and six cases of peritoneal tearing occurred (30% in the recurrent hernia group and 7.8% in the primary hernia group), but this was similar or even lower, compared to the rate of peritoneal tearing, in other studies (26% in the adhesions group versus 18% in the no-adhesions group 5 and 46% in the recurrent hernia group versus 28% in the primary hernia group 13 ).…”
Section: Discussionmentioning
confidence: 56%
“…The recurrence rate after laparoscopic TEP repair for recurrent inguinal hernia was not higher than that after primary hernia repair, and it even reached 0% in some studies. 5,13,14 Lowham et al 15 reported that a major cause for recurrence after laparoscopic TEP repair was technical errors, including inadequate dissection of the space, an insufficient size of the prosthesis, and incorrect mesh positioning. Dissection and making a space are more difficult in patients with recurrent inguinal hernia due to adhesion and the hard scar tissue, and the recurrence rate after hernioplasty could be higher for recurrent inguinal hernia than that for primary inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the difficult dissection because of scar tissue and the frequently altered anatomy [5].…”
mentioning
confidence: 99%